Removal of Zinc by adsorption on macroalgae as adsorbent from aqueous solution - Camurati, Julieta R. (2021)
Discharge of industrial and domestic effluents in environment is responsible forthe presence of toxic metals in water, soil and biota. Biosorption, with deadbiomass, is a process that allows the passive capture of metal ions by differentmechanisms. The objective was to evaluate the use of dry macroalgae in zincremoval from aqueous solution. The effect of alga species, pH, initial adsorbateand adsorbent concentration were evaluated. Results showed that Zn removalefficiency was higher when Halymenia sp. (red alga) was used instead Ulvalactuca (green alga). This could be related to the different cell wall compositionfor each algae class. The increase of the adsorbent mass improved the efficiency,and more acidic pHs decreased it. We concluded that algae are an interestingbiomass for the removal of zinc.